Implementation of a surgical site infection prevention bundle: Patient adherence and experience - Stacey Hockett Sherlock; Daniel Suh; Eli Perencevich; Heather Schacht Reisinger; Judy Streit; Amy Frank; Gosia Clore; Madeline Ohl; Dina Speicher; Loreen Herwaldt; Marin L. Schweizer (Cambridge University Press, 2021)
We evaluated barriers and facilitators to patient adherence with a bundled intervention including chlorhexidine gluconate (CHG) bathing and decolonizing Staphylococcus aureus nasal carriers in a real-world setting. Survey data identified 85.5% adherence with home use of CHG as directed and 52.9% adherence with home use of mupirocin as directed.